Ann Suter, The Narcissus and the Pomegranate: An Archaeology of the Homeric Hymn to Demeter - Pike, Sarah M (Pomegranate, 2007)
Ann Suter, The Narcissus and the Pomegranate: An Archaeology of the Homeric Hymn to Demeter (Ann Arbor: University of Michigan Press, 2002), 328 pp., 65 (cloth).